MECANISMES D’ELIMINATION D’ACIDES ORGANIQUES AROMATIQUES PAR LE SULFATE D’ALUMINIUM ET EFFET DE LA MINERALISATION Removal mechanisms of acid aromatic organics by aluminium sulphate and mineralization effect - ASSIA, REZEG; SAMIA, ACHOUR (Courrier du Savoir, 2014)
The aim of this work was to study removal of aromatic organic molecules in distilled water by aluminium sulphate. Coagulation-flocculation of these compounds highlighted the complexity of the involved mechanisms and their close dependence on nature and number of acid groups substituting the aromatic ring. The position of substituents one over the other appeared to contribute evenly to explain the differences in the disposal yields observed. The adsorption could be the predominant mechanism during the coagulation-flocculation of gallic acid and pyrogallol. In addition, removal of pyromellitic acid at pH = 5.5, can be explained by the existence of chemical interactions between the pyromellitic acid and the cationic soluble species of aluminum. When these organic compounds were dissolved in mineralized groundwater, the results showed that the water mineralization could be have promoter or inhibitor impact according to the structure of the organic compounds tested. Thus, compounds with hydroxyl function (pyrogallol and gallic acid) beheld their disposal yields increase from the water Ifri (Conductivity = 0.64ms/cm; TH = 48 o F) to the water of Biskra the most mineralized (Conductivity = 4.75ms/cm; TH = 208 o F). The increased mineralization appeared also inhibit the elimination of salicylic acid and especially that of acid pyromellitic.   L’élimination de molécules organiques aromatiques en eau distillée par coagulation-floculation au sulfate d`aluminium a mis en évidence la complexité des mécanismes mis en jeu et leur étroite dépendance de la nature et du nombre de groupements acides substituant le cycle aromatique. La position des substituants l’un par rapport à l’autre a semblé contribuer également à expliquer les différences de rendements d’élimination observés. L’adsorption pourrait être le mécanisme prédominant au cours de la coagulation-floculation de l’acide gallique et du pyrogallol. Par ailleurs, l’élimination de l’acide pyroméllitique à pH=5,5, peut s’expliquer par l’existence d’interactions chimiques entre l’acide pyroméllitique et les espèces solubles cationiques de l’aluminium. Lorsque ces composés organiques ont été dissous dans des eaux souterraines naturellement minéralisées, les résultats ont montré que la minéralisation de l’eau pouvait avoir un effet promoteur ou inhibiteur selon la structure du composé organique testé. Ainsi, les composés fortement hydroxylés (phloroglucinol, pyrogallol et l’acide gallique) ont vu leurs rendements d’élimination augmenter en passant de l’eau Ifri (Conductivité=0.64ms/cm ; TH=48o F) à l’eau de Biskra la plus minéralisée (Conductivité =4,75ms/cm ; TH= 208o F). La minéralisation croissante a semblé par ailleurs, inhiber l’élimination de l’acide salicylique et surtout celle de l’acide pyroméllitique.